2017
DOI: 10.1080/19336896.2017.1336274
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and pathology of prion protein amyloid accumulation and cellular damage in extraneural tissues of scrapie-infected transgenic mice expressing anchorless prion protein

Abstract: In most human and animal prion diseases the abnormal disease-associated prion protein (PrPSc) is deposited as non-amyloid aggregates in CNS, spleen and lymphoid organs. In contrast, in humans and transgenic mice with PrP mutations which cause expression of PrP lacking a glycosylphosphatidylinositol (GPI)-anchor, most PrPSc is in the amyloid form. In transgenic mice expressing only anchorless PrP (tg anchorless), PrPSc is deposited not only in CNS and lymphoid tissues, but also in extraneural tissues including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Amyloid fibrils are highly structured, densely packed protein aggregates 10 which have been found in amyloid-plaques in patients with neurodegenerative disorders 11 . Their cytotoxic effect was also shown on numerous occasions with both in vitro [12][13][14] and in vivo 15,16 experiments. It has been observed that prion protein amyloid fibrils can exist in multiple distinct structural conformations [17][18][19] .…”
mentioning
confidence: 80%
“…Amyloid fibrils are highly structured, densely packed protein aggregates 10 which have been found in amyloid-plaques in patients with neurodegenerative disorders 11 . Their cytotoxic effect was also shown on numerous occasions with both in vitro [12][13][14] and in vivo 15,16 experiments. It has been observed that prion protein amyloid fibrils can exist in multiple distinct structural conformations [17][18][19] .…”
mentioning
confidence: 80%